Predicting Delinquency Levels in Turkish Adolescents - Yuksel-Sahin, Fulya (ELSEVIER SCIENCE BV, 2013)
The study aims to determine how the variables of peer deviance, gender, and grade level, having, too many problems, parental divorce, and guidance by the school counsellor about delinquency contribute to predicting delinquency levels in adolescents. The research was conducted upon 277 adolescents. The Delinquency Scale, The Peer Deviance Scale, and a Personal Information Form were used to obtain data. The collected data were analysed by multiple regression analysis. The research revealed that the variables of peer deviance, gender, grade level, having too many problems, and parental divorce are significant predictors of adolescent delinquency, while guidance by the school psychological counsellor about delinquency as a variable does not constitute a significant predictor. (C) 2013 The Authors. Published by Elsevier Ltd.
Keywords: Delinquency Behaviour; Peer Deviance; Adolescent; Education & Educational Research